P PERAN PEMERINTAH KABUPATEN LOMBOK TIMUR DALAM PERLINDUNGAN ANAK DI BIDANG PENDIDIKAN : The Role Of The Lombok Timur Regency Government In Child Protection In The Education Field - Saleh, Muhammad; Bayu, Bayu Pratondo; Heri, Heri Dudiatman (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2023)
Education is a very important human need because education has the task of preparing human resources for the development of the nation and state. Advances in science and technology (IPTEK) result in changes and growth in a more complex direction. Dropping out of school is not a new problem in the history of education. This type of research is field research, namely research carried out systematically and methodologically to reveal the data required in research that originates from the location or field. The factor of lack of education is the child's awareness of the importance of education for his future and the lack of motivation within the child. The East Lombok Regency Government is expected to continue to collect data on out-of-school children in each area of ​​the Lombok Timur Regency evenly. This data is then used as a basis for formulating a policy. The Lombok Timur Regency Government needs to continue to carry out outreach to increase public awareness regarding the importance of going to school in every corner of the Lombok Timur Regency and that its implementation is sustainable.